PERFORMANCE ANALYSIS ONAIR-CONDITIONING DOME BY STAR-CCM+ - JI FangFang; JIANG LiFei (Jixie qiangdu)
Three kinds of air conditioning shroud are analyzed by using STAR-CCM+. The results show that the scheme 2 with circular arc surface structure on both windward and the scheme 3 with circular arc surface structure only on windward side are better. The data is verified by comparing with the wind tunnel test data without cross-wind condition. The influence of different diversion hood shapes on the intake and exhaust air of condenser and fresh air intake was evaluated by calculating the pressure distribution of intake and exhaust outlets of schemes 2 and 3. It provides a basis for the design of air conditioning shroud.